Pengembangan Media Dakon Matematika (Dakota) Pada Materi FPB dan KPK Untuk Meningkatkan Minat Belajar Pada Siswa Kelas IV SD Inpres Paccerakkang - Rahmah Kumullah; Amrullah Mahmud (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
This study aims to describe the procedure, to determine the quality of the product, to describe the level of student interest in mathematics in FPB and KPK. This research uses research and development methods. This research stage refers to the development stage according to ADDIE. The subjects of this study were fourth grade students of SD Inpres Paccerakkang who were suspected of being 12 people as the sample. The data analysis technique used in this research is qualitative analysis and quantitative analysis. The two analyzes were carried out simultaneously. Based on the results of the validation, two instructional media experts gave an average score of 43 (SB) and 44 (SB) while the class teacher gave an average score of 41 (B) and 42 (SB). Furthermore, for small group trials it has increased. This is shown in the pretest obtained 58% or as many as 7 students who are complete while the posttest increase in completeness reaches 100% because all students complete in learning. Then student interest in learning also increased after the use of Dakota media that had been developed. This is shown in the average value of student interest in learning is 81 which is very good category.